Evaluation of periodontally diseased molars in diabetics with Miller-McEntire Periodontal Prognostic Index - Dharmarajan Gopalakrishnan; Preston Dallas Miller; Amit Vasant Mahuli; Sidharthan Sangamithra; Prathip Phantumvanit; Borvornwut Buranawat (Wolters Kluwer Medknow Publications, 2018)
Aim and Objective: The aim of this study was to prospectively determine and establish the periodontal prognosis of diseased molars in diabetic patients using the Miller-McEntire Periodontal Prognostic Index (MMPPI) with an additional criterion for diabetes (changes in glycosylated hemoglobin levels), at 2-year postperiodontal therapy. Materials and Methods: A sample of 200 molars in 25 patients with diabetes mellitus (DM) and chronic periodontitis were evaluated. The prognostic parameters evaluated include age, probing depth (PD), mobility, furcation involvement, diabetes, and molar type. The total score calculated from all parameters was used considered prognosis score for each molar. All patients were evaluated at baseline and 2-year posttreatment. Results: The results of this study suggest that following prognostic factors, DM (hazard ratio [HR] =5.2), age (HR = 0.4), and molar type (HR = 0.6) were clinically significant at the end of the 2-year posttherapy from baseline. A total of 4 (2%) teeth were extracted from the 200 teeth with a mean of 0.02 for the tooth lost during 2-year posttreatment. Significant improvements (P < 0.05) in the frequency PD, furcation, and mobility scores were noted at 2 years. Conclusions: These findings demonstrate that score for DM as prognostic criterion is a valid addition to MMPPI. The factors such as DM, age, and molar type can impact the prognosis of molar survival. Studies with a larger sample size and longer follow-up are required to affirm the findings of this preliminary study.